Use of the Roguelike genre as a narrative tool: Memories and child development in The Binding of Isaac - Goulin, Júlia Ruiz S.; Mota, Rosilane Ribeiro da (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
The use of mechanics to tell stories and enrich a narrative is not a new concept at all, it is commonly used in games to deepen the immersion and to create a more cohesive work. This paper however uses Piaget´s development theory to explore and understand the use of the game genre itself as a narrative tool to bring to life the view of a five-year-old child o n his own terms, not a look from the outside, but from inside the child’s mind.